The pro‐fibrotic role of dipeptidyl peptidase 4 in carbon tetrachloride‐induced experimental liver injury. Issue 5 (20th December 2016) - Wang, Xin M; Holz, Lauren E; Chowdhury, Sumaiya; Cordoba, Shaun P; Evans, Kathryn A; Gall, Margaret G; Vieira de Ribeiro, Ana Júlia; Zheng, Yuan Zhou; Levy, Miriam T; Yu, Denise MT; Yao, Tsun‐Wen; Polak, Natasa; et al.
Abstract : Liver fibrosis is a progressive pathological process involving inflammation and extracellular matrix deposition. Dipeptidyl peptidase 4 (DPP4), also known as CD26, is a cell surface glycoprotein and serine protease. DPP4 binds to fibronectin, can inactivate specific chemokines, incretin hormone and neuropeptides, and influences cell adhesion and migration. Such properties suggest a pro‐fibrotic role for this peptidase but this hypothesis needs in vivo examination. Experimental liver injury was induced with carbon tetrachloride (CCl4 ) in DPP4 gene knockout (gko) mice. DPP4 gko had less liver fibrosis and inflammation and fewer B cell clusters than wild type mice in the fibrosis model. DPP4 inhibitor‐treated mice also developed less liver fibrosis. DNA microarray and PCR showed that many immunoglobulin (Ig) genes and some metabolism‐associated transcripts were differentially expressed in the gko strain compared with wild type. CCl4 ‐treated DPP4 gko livers had more IgM + and IgG + intrahepatic lymphocytes, and fewer CD4 +, IgD + and CD21 + intrahepatic lymphocytes. These data suggest that DPP4 is pro‐fibrotic in CCl4 ‐induced liver fibrosis and that the mechanisms of DPP4 pro‐fibrotic action include energy metabolism, B cells, NK cells and CD4 + cells.